PENGARUH PENGIMBASAN ASAM SALISILAT TERHADAP TANAMAN CASSAVA Manihot esculenta Crantz TAHAN Fusarium oxysporum BERDASARKAN JUMLAH DAUN, INDEKS STOMATA DAUN DAN KADAR SENYAWA FENOL - Nurcahyani, Endang; Irawan, Bambang; Yulianty; Wahyuningsih, Sri; Agustin, Resya Tamara; Yuniar, Lutfiah; Dewiyatno, Rezza Kusumma (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Cassava (Manihot esculenta Crantz) is a plant that is widely cultivated in Indonesia, this is because cassava is one of the staple food sources and sources of income throughout the tropics, but in the planting process, farmers are often constrained by attacks by pathogenic fungi that cause fusarium wilt disease and cause the quality of cassava plants to decline. One way to control this disease is by selecting cassava plants in the planting medium in vivo through salicylic acid infiltration to increase resistance to pathogens and improve the quality of cassava plants. The purpose of this study was to determine the effect of salicylic acid on the number of leaves, leaf stomatal index, and phenol content of cassava plants resistant to Fusarium oxysporum compared to controls. This study used a one-factor Completely Randomized Design (CRD) with 5 levels of salicylic acid concentration, namely 0 ppm, 80 ppm, 100 ppm, 120 ppm and 140 ppm. Data analysis using Analysis of Variance (ANOVA) and further testing with Tukey test at the 5% level. The results showed that the concentration of salicylic acid that was tolerant for cassava plant selection with optimum growth was 100 ppm which was indicated by an increase in the number of leaves and leaf stomata index while the most optimum concentration of salicylic acid for increasing phenol levels was 140 ppm Keywords: salicylic acid, cassava, Fusarium oxysporum, induced resistance